Synthesis of nanofluids containing eco-friendly functionalized carbon nanomaterials for improving heat dissipation / Rad Sadri - Rad, Sadri (2018)
Conventional working fluids used in high heat flux systems such as heat exchangers and solar collectors typically have low thermal conductivities which provides low heat transfer efficiency. Many studies have been performed to improve the heat transfer of the conventional working fluids by dispersing higher thermally conductive particles into them. In this study, highly conductive carbon nanostructures are dispersed in distilled (DI) water, and the thermal properties are significantly enhanced at the lowest particle concentration. This study is focused on the development of eco-friendly, facile, functionalization technique to synthesize a new generation of water-based carbon nanostructure nanofluids for use as coolants in order to improve the convective heat transfer and hydrodynamic properties of a single-tube heat exchanger. The approach is green since it does not involve the use of toxic, corrosive acids. The graphene nanoplatelets (GNPs) and multi-walled carbon nanotubes (MWCNTs) were covalently functionalized using clove buds and gallic acid, respectively, using the one-pot method. Next, the functionalized GNPs and MWCNTs were dispersed in DI water to synthesize the clove-treated GNP, gallic acid-treated GNP, gallic acid-treated MWCNT nanofluids. Moreover, graphene oxide was reduced using saffron in one pot to synthesize water-based saffron-reduced graphene oxide (SrGO). The nanofluids were produced at various particle concentrations (0.025, 0.075, and 0.1 wt %). The effectiveness of the covalent treatment and reduction method were evaluated using Fourier transform infrared spectroscopy, Raman spectroscopy, thermogravimetric analysis, X-ray photoelectron spectroscopy, transmission electron microscopy, and ultraviolet-visible spectroscopy. Ultraviolet-visible spectroscopy and zeta potential measurements were also conducted to verify the colloidal stability and the presence of hydrophilic groups on the surface of the functionalized nanoparticles. The thermo-physical characteristics of the nanofluids were investigated experimentally and the results indicate there is significant thermal conductivity enhancement (up to 29.2%) for the water-based SrGO at 45°C. The turbulent convective heat transfer was studied using a heat exchanger subjected to constant heat flux (12,752 W/m2) within a Reynolds number range of 6,371–15,927. Preliminary experiments were conducted with DI water and the results were compared with those determined from empirical correlations. The results indicate good reliability and accuracy of the set-up. Experiments were conducted for the nanofluids flowing through the loop under fully-developed turbulent condition and the results show that the addition of a low fraction of green-functionalized carbon nanostructures into DI water significantly enhances the Nusselt number and convective heat transfer coefficient (up to 40% for water-based SrGO). The increase in friction factor and relative pumping power (<1.21) is negligible. The remarkable enhancement of the performance index (>1) indicates that these nanofluids have great potential for use as heat transfer fluids considering the overall thermal performance and energy savings. The computational fluid dynamics (CFD) simulation are performed using shear stress transport k-ω turbulence model to predict the heat transfer performance of water-based CGNPs nanofluids in three-dimensional heated tube. The results conform well to those from experiments with an average relative deviation of ±10. The experimental results confirm the applicability of the numerical model to simulate heat transfer performance of nanofluids in turbulent flow conditions.